The Impact Of Democratic Leadership Style And Work Conflict On Employee Performance At PT. Victory International Futures Spazio Surabaya - Vaneza Sabatimy; Mei Retno Adiwat (International Forum of Researchers and Lecturers, 2024)
The objective of this study is to analyze how the democratic leadership style and work conflict impact the performance of employees at the Surabaya Branch of PT Victory International Futures. This study adopts a quantitative methodology by gathering primary data through questionnaires using Google Form, employing a 5-point Likert scale. The data was collected from 74 respondents and interviews were conducted with the HRD of PT Victory International Futures Spazio Surabaya. Secondary data is gathered from various sources like books, articles, journals, and theses that delve into this particular research topic. The data was analyzed through Partial Least Square (PLS) which revealed that the performance of employees is mainly impacted by factors such as democratic leadership style and work conflict, while other variables beyond the research model also play a role. The findings revealed that the democratic leadership style contributes positively and significantly to performance, while work conflict also has a positive and significant impact on performance.